2022
DOI: 10.3390/cryst12111552
|View full text |Cite
|
Sign up to set email alerts
|

Physical-Mechanical Properties of Chartwell® Coupling Agent-Treated Calcium Carbonate and Silica-Reinforced Hybrid Natural Rubber Composites

Abstract: In this work investigated the possibility of applying a superficial treatment to ultra-fine calcium carbonate aiming to improve its interaction with the polymer chains of natural rubber so it does not act just as a filler. Commercial processes commonly use 40 phr of Silica as reinforcement filler. Here, we have evaluated the partial replacement of Silica by two types of calcium carbonate into hybrid natural rubber composites, untreated ultra-fine calcium carbonate and with ultra-fine calcium carbonate treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…The formation of the Si–O bond results in a shift of the Si–O stretching vibration. Ribeiro et al 48 demonstrated interaction between ultra-fine calcium carbonate and natural rubber by applying a superficial treatment to the calcium carbonate which provides materials with improved properties. They observed the similar bonds between coupling agents and calcium carbonate groups.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the Si–O bond results in a shift of the Si–O stretching vibration. Ribeiro et al 48 demonstrated interaction between ultra-fine calcium carbonate and natural rubber by applying a superficial treatment to the calcium carbonate which provides materials with improved properties. They observed the similar bonds between coupling agents and calcium carbonate groups.…”
Section: Resultsmentioning
confidence: 99%